The olfactory bulb in newborn piglet is a reservoir of neural stem and progenitor cells. - Lee J Martin (Public Library of Science (PLoS), 2013)
The olfactory bulb (OB) periventricular zone is an extension of the forebrain subventricular zone (SVZ) and thus is a source of neuroprogenitor cells and neural stem cells. While considerable information is available on the SVZ-OB neural stem cell (NSC)/neuroprogenitor cell (NPC) niche in rodents, less work has been done on this system in large animals. The newborn piglet is used as a preclinical translational model of neonatal hypoxic-ischemic brain damage, but information about the endogenous sources of NSCs/NPCs in piglet is needed to implement endogenous or autologous cell-based therapies in this model. We characterized NSC/NPC niches in piglet forebrain and OB-SVZ using western blotting, histological, and cell culture methods. Immunoblotting revealed nestin, a NSC/NPC marker, in forebrain-SVZ and OB-SVZ in newborn piglet. Several progenitor or newborn neuron markers, including Dlx2, musashi, doublecortin, and polysialated neural cell adhesion molecule were also detected in OB-SVZ by immunoblotting. Immunohistochemistry confirmed the presence of nestin, musashi, and doublecortin in forebrain-SVZ and OB-SVZ. Bromodeoxyuridine (BrdU) labeling showed that the forebrain-SVZ and OB-SVZ accumulate newly replicated cells. BrdU-positive cells were immunolabeled for astroglial, oligodendroglial, and neuronal markers. A lateral migratory pathway for newly born neuron migration to primary olfactory cortex was revealed by BrdU labeling and co-labeling for doublecortin and class III β tubulin. Isolated and cultured forebrain-SVZ and OB-SVZ cells from newborn piglet had the capacity to generate numerous neurospheres. Single cell clonal analysis of neurospheres revealed the capacity for self-renewal and multipotency. Neurosphere-derived cells differentiated into neurons, astrocytes, and oligodendrocytes and were amenable to permanent genetic tagging with lentivirus encoding green fluorescent protein. We conclude that the piglet OB-SVZ is a reservoir of NSCs and NPCs suitable to use in autologous cell therapy in preclinical models of neonatal/pediatric brain injury.